Branding Product Pelaku Usaha Mikro Kecil Menengah Kuningan Barat Jakarta Selatan - Muhammad Saifulloh (Universitas Prof. Dr. Moestopo (Beragama), 2021)
Micro, Small and Medium Enterprises (MSMEs) have an important role in improving the Indonesian economy. MSMEs are not affected by external pressure so that they are able to survive and grow during the Covid-19 pandemic crisis. MSME actors are constrained by product marketing, do not understand the benefits of branding, lack of knowledge of branding, do not have a positive entrepreneurial character and what is no less important is that they have not received training or assistance regarding technical branding strategies for MSME players. In marketing communication, one of the functions of branding is as a means to instill a positive image in the minds of consumers, so that it needs to be understood by MSME players, because product branding is one of the important points so that UMKM products will always be remembered by the public or consumers within a period of time. which is old.